Plano de projeto para implementação de um roteiro turístico no vilarejo de Santo Amaro do Sul - Tagliaro, Ana Cláudia Travassos (Universidade do Vale do Rio dos Sinos, 2017)
The main objective of this final paper is to present a project plan for the development and implementation of a tourist itinerary in the village of Santo Amaro do Sul, a village that has as a highlight the architectural beauty of the buildings built by the Azorean settlers and listed as National Historic Patrimony. The present final paper will address and present the management plan of scope, time, quality, risks, resources, communications and acquisitions, mirrored in the PMBOK good practices, to describe the plan of how the project should be set up.
Keywords: Plano de gerenciamento do projeto; Roteiro turístico; Escopo do projeto; Project management planning; Tourist route; Project scope